Science and the COVID-19 recovery fund: The time for public health and international health diplomacy?! - Florian Fischer (Elsevier, 2021)
Currently, social and political discussions are dominated by aspects related to the handling of the COVID-19 pandemic. Several approaches for supporting science in times of COVID-19 have been undertaken at the national and supranational level, such as the COVID-19 recovery fund by the European Union. For reducing the global disease burden and the societal burden related to economic crises caused by the COVID-19 pandemic, adequate political and financial support is needed. This is closely related to funding of research and programs for absorbing the adverse effects of the pandemic and the measures introduced to diminish the spread of the disease. This contribution highlights the relevance of public health research and international health diplomacy to evaluate the direct and indirect impacts of COVID-19 on populations health.